DEVELOPMENT OF A RELIGIOUS TOURISM MANAGEMENT INFORMATION SYSTEM AT K.H.R BAGUS KHASANTUKA TOMB IN SENUKO SIDOAGUNG - Aisyiyah Faj'ri Nur Jannah; Muhammad Fairuzabadi (CV. Fahr Publishing, 2025)
The management of religious tourism at the K.H.R Bagus Khasantuka Tomb in Senuko Sidoagung faces several challenges, particularly in financial recording, human resource management, and the documentation of history and oral traditions. This study aims to develop a Religious Tourism Management Information System to enhance operational efficiency and support cultural heritage preservation. The development methodology follows the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance. The system was evaluated using Black Box and Alpha Testing methods to assess functionality and user experience. The results indicate that the developed system improves financial transparency, facilitates visitor data recording, and supports historical and traditional documentation more effectively. This system modernizes and structures religious tourism management, with the potential to increase visitor engagement.